2016
DOI: 10.1007/s10047-016-0900-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of albumin leakage in hemodialysis patients on redox status of serum albumin

Abstract: Human mercaptoalbumin (HMA) is a reduced form of albumin that is associated with cardiovascular disease in dialysis patients. Albumin-leaky hemodialysis (HD) is increasingly recognized as a gold standard therapy because it is correlated with better prognosis compared to conventional HD. However, albumin-leaky HD induces low serum albumin concentration because of albumin leakage, which is a classical risk factor for mortality. The aim of this study was to explain the preferable prognosis in patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…When we try to remove larger LMWPs, we have to accept ∼3–5 g of albumin leakage and, occasionally, this may be >10 g in some circumstances [ 67 ]. Nagai et al [ 68 ] reported that dialysis modalities with ≥3 g of albumin loss during a dialysis session had better survival rates than those with <3 g. They also reported that protein-leaking dialysis was favorable to maintain the serum level of the reduced form of albumin, which was recognized as having protective effects on dialysis patients from cardiovascular events [ 69 ]. However, large amounts of albumin leakage should be avoided because this leads to hypoalbuminemia and lipoprotein metabolism abnormalities.…”
Section: Present Status Of Protein-permeable Dialysis In Japanmentioning
confidence: 99%
“…When we try to remove larger LMWPs, we have to accept ∼3–5 g of albumin leakage and, occasionally, this may be >10 g in some circumstances [ 67 ]. Nagai et al [ 68 ] reported that dialysis modalities with ≥3 g of albumin loss during a dialysis session had better survival rates than those with <3 g. They also reported that protein-leaking dialysis was favorable to maintain the serum level of the reduced form of albumin, which was recognized as having protective effects on dialysis patients from cardiovascular events [ 69 ]. However, large amounts of albumin leakage should be avoided because this leads to hypoalbuminemia and lipoprotein metabolism abnormalities.…”
Section: Present Status Of Protein-permeable Dialysis In Japanmentioning
confidence: 99%
“…The maximum admissible amount of albumin leakage remains unclear. However, we have already clarified that HD with 9.1 g albumin leakage per HD session for 1 month may induce a significant decrease of serum albumin and increase of serum total cholesterol, even though the level of the reduced form of albumin remained stable, which is associated with cardiovascular disease in dialysis patients . Dyslipidemia can be harmful in patients undergoing albumin leaky HD.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm proposed is based on some arbitrary, or unproven assumptions: Albumin is the most relevant prognostic marker in both HDF and HD [ 70 , 71 , 72 , 73 ]; Albumin loss is non-selective, and low serum albumin levels have to be avoided [ 74 , 75 , 76 , 77 , 78 ] (i.e., “toxic albumin”, is not selectively lost; toxic albumin is albumin-linked to uremic toxins, for which loss should be promoted according to some authors [ 73 , 74 ]; Different dialyzers in the same category are equivalent (high-, medium- or low-flux) in terms of performance and albumin leakage (while this is not entirely true, a detailed discussion is beyond the scope of this review); Loss of albumin is higher in the first minutes of HDF, supporting the choice of low-permeability membranes in the case of more frequent dialysis [ 74 ]; Loss of albumin is also a marker of loss of other potentially useful nutrients, including vitamins; such a loss may contribute to malnutrition; Adsorption by dialysis membranes is not a relevant element in the removal of uremic toxins; if present, it is similar in similar categories of dialyzers [ 78 ]. …”
Section: Arbitrary (Or Unproven) Assumptionsmentioning
confidence: 99%
“…Albumin loss is non-selective, and low serum albumin levels have to be avoided [ 74 , 75 , 76 , 77 , 78 ] (i.e., “toxic albumin”, is not selectively lost; toxic albumin is albumin-linked to uremic toxins, for which loss should be promoted according to some authors [ 73 , 74 ];…”
Section: Arbitrary (Or Unproven) Assumptionsmentioning
confidence: 99%